Integration or Segregation? (Teachers’ Perception on the Use of Whole Language Method) - Istiqlaliah Nurul Hidayati; Deddy Sofyan (English Department - University of Sultan Ageng Tirtayasa, 2018)
The research is aimed at finding out the perception of English Education Study Program lecturers on the teaching and assessment of language skills whether they need to be taught in segregation or integration. The respondents of the research were 68 lecturers of English Education Study programs united at APSPBI, an association of English Education Study Program. The research employed descriptive method with the instruments of online questionnaires, interview, and documentation. The online questionnaires consisted of six questions and they were spread out through social media. The interview was conducted to five lecturers of different universities and the documents analyzed were books on speaking, reading, listening and writing skills used at the universities where the respondents teach. The result shows that 80% of the respondents still teach the English skills separately. However, 64% from the total number agree that the skill should be taught in integration. 50% of books used by the lecturers are integrated. Even though mostly the lecturers agree to the skills integration, in fact some of them still find themselves focusing on one skill to be emphasized in one meeting. Mostly the lecturers prefer the assessment to be conducted in integration yet most of the books still separate the assessment based on the skills.